The relationship between senses of humor and Mindfulness with Anxiety of death in elderly men refer to Jahandidegan center of seven region of Municipality in Tehran city - Elahe Hosseinzadeh; Anahita Anahita Khodabakhshi-koolaee (Mashhad University of Medical Sciences, 2017)
Background and objective: Ageing period is a time to encounter the facts of life like the death. The acceptance of the reality for all of elders is not easy, but some of research evidences indicated that the two psychological elements including; the sense of humor and mindfulness can be reducing the anxiety of death. The main aim of this study was to assess the relationship between senses of humor and mindfulness with anxiety of death in elderly men. Methods: The current study is descriptive with Correlation .The statistical research community included; all elderly men of District 7 and the Jahandidegan (Ageing) centers of Tehran Municipality in 1394-95. The sample statistical of present research of 100 people between 65 to 75 years old of elderly men by “Available sampling method”. Data collection tools include mental state examination (MMSE), Screening subjects and Sense of Humor Questionnaire (SHQ), Mindfulness questionnaire and Templar Death Anxiety Inventory (DAS). In order to analyze data from tables’ descriptive statistics, Pearson correlation and stepwise regression were used. Results: The results showed that between senses of humor and mindfulness there is a significant negative relationship with death anxiety. The results show that the total variable used to predict 28% of the variance in death anxiety. Humor also has higher effective rate on death anxiety of in elderly men prediction. Conclusion: The findings of present study revealed that the psychological components like; sense of humor and mindfulness can be reduce the anxiety of death in male elderlies. Therefore, elderly counselors and clinicians could be used these two elements for reduction most of anxiety including; the death.  Paper Type: Research Article